Risk Factors of Death in Chronic Obstructive Pulmonary Disease (COPD) Patients at Dr. Soetomo General Academic Hospital, Surabaya, in 2019 - Wedhana, Hilmy Indra; Bakhtiar, Arief; Kusuma, Edward; Rosyid, Alfian Nur (Universitas Airlangga, 2025)
Highlights: The highest distribution of chronic obstructive pulmonary disease (COPD) patients’ age and gender was over 60 years old and males. The highest distribution of COPD patients’ comorbidity was infection, with pneumonia being the most common infection. Abstract Introduction: The distribution of death and risk factors in chronic obstructive pulmonary disease (COPD) patients varies according to disease severity. This study aimed to determine the risk factors of mortality in COPD patients. Methods: This was a retrospective descriptive study with a total sampling method using inclusion and exclusion criteria. Data collection was performed on patients' medical records throughout 2019. The inclusion criteria for this study sample were patients diagnosed with COPD who died in 2019, aged over 25 years old (adults), both male and female. The exclusion criteria were COPD patients with incomplete medical record data. Results: The total number of samples obtained and included in this study was 31 COPD patients (n=31). The characteristics of the patients showed a predominance of males over females, with a ratio of 9:1. Seventeen samples (58.0%) out of 31 were patients aged >66 years old. Comorbidities accounted for 96.8% of the study population. The most prevalent comorbidity was infection (77.41%), with pneumonia accounting for 38.7% of all deaths. Eighteen patients (58.1%) reported having two or more comorbidities, whilst 28 patients (90.3%) scored 0-7 on the Modified Sequential Organ Failure Assessment (mSOFA) when admitted to the hospital. Conclusion: This study found that the group of patients with the mSOFA score of 0-7 with the characteristics of being aged >60 years old, males, and having pneumonia infection had the highest mortality rate among other COPD patients who died.